The effect of bevel angle on apical microleakage following the use of amalgam and MTA - Sharifian MR; Motahhari P; Shahsia S (Tehran University of Medical Sciences, 2006)
Background and Aim: Achieving appropriate seal in canal obturation is the main goal of endodontic therapy. However, in some cases, it can not be obtained by non-surgical procedures alone. Retrograde surgery is one of the most common procedures in endodontics. Apical seal improvement can be obtained by root end filling and decreasing the root end resection angle (bevel angle). The aim of this study was to investigate the role of bevel angle on apical microleakage following the use of amalgam and MTA as root end filling materials. Materials and Methods: In this experimental study, 128 extracted human teeth were instrumented and obturated by lateral condensation technique. The teeth were divided into two groups and the apical root resection was performed by high speed fissure bur (one group perpendicular to the long axis of the teeth and the other 45 to the long axis. The 3 mm root end cavity was prepared by ultrasonic device. Each group was divided into two subgroups: One filled with amalgam and the other with MTA. Teeth were incubated for 72 h, covered by two layers of nail polish (except for apical 3mm) and submerged in methylene blue for 48 h. Teeth were washed under tap water and mesiodistally dissected by low speed disc. Dye penetration was evaluated by stereomicroscope. Data were analysed by two way ANOVA and Tukey tests with p<0.05 as the limit of significance. Results: The results showed that retrofill material type had a significant effect on microleakage and MTA was superior to amalgam in this respect. Bevel angle failed to show any significant effect on apical microleakage. Conclusion: Based on the results of this study, it seems that the use of MTA instead of amalgam in clinical practice can improve the success rate of endodontic surgery whereas the bevel angle can be determined based on the status of each individual case; However, increasing the bevel angle seems to increase microleakage due to exposure of more dentinal tubules.